Synthesis and Characterization of Niobium Aluminium Carbide - Gorsi, Monika (My University, 2016)
Due to the versatile properties like elastic stiffness, good thermal and electrical conductivity, resistance to chemical attack, and low thermal expansion coefficients, MAX phases have become a special group of compounds. They combine properties of both metals and ceramics so they find many applications in industries and aerospace. Among the large family of MAX phases, Nb2AlC is potential candidate for high temperature applications. Therefore, in present study it was attempted to synthesise Nb2AlC by ball milling using niobium pentaoxide (Nb2O5), activated charcoal as a carbon source, aluminium metal powder and magnesium as a reducing agent. The as-prepared samples were characterized and studied by X-ray powder diffraction, Field emission scanning electron microscopy and high resolution transmission electron microscopy at room temperature. Milling time and amount of reducing agent were optimized for the synthesise of Nb2AlC. However, no signature of Nb2AlC was observed in the synthesized samples and the resultant product is a nanocomposite comprising of NbC and Al2O3.
Keywords: Max Phase; Nano material; Ball Milling; Synthesis